Primary minerals of the Jachymov ore district - Ondrus,P.; Veselovsky,F.; Gabasova,A.; Hlousek,J.; Srein,V.; Vavrin,I.; Skala,R.; Sejkora,J.; Drabek,M. (Journal of the Czech Geological Society, 2003)
One hundred and seventeen primary mineral species are described and/or referenced. Approximately seventy primary minerals were known from the district before the present study. All known reliable data on the individual minerals from Jachymov are presented. New and more complete X-ray powder diffraction data for argentopyrite, stembergite, and an unusual (Co,Fe)-rammelsbergite are presented. The following chapters describe some unknown minerals, erroneously quoted minerals and imperfectly identified minerals. The present work increases the number of all identified, described and/or referenced minerals in the Jachymov ore district to 384.
Keywords: Primary minerals; XRD; microprobe; unit-cell parameters; Jachymov